Development of hypertensive animal model using ovariectomised rat fed with short-term 2% cholesterol diet - Kumeshini S,; Nurshazana A,; Faizah Othman,; Kamsiah Jaarin,; Srijit Dass,; Zar, Chi Thent (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Menopause, a cessation of menstrual bleeding, is directly related to serious illness confined to cardiovascular disease (CVD) such as hypertension and stroke. The oestrogen withdrawal and consumption of high cholesterol diet has a detrimental effect on cardiovascular function and metabolism in menopausal women. The present study was aimed to develop the hypertensive rat model in the ovariectomised Sprague Dawley rats fed with 2% cholesterol diet following a short term period. Eighteen Sprague-Dawley rats were randomly divided into three groups; Sham control (sham), ovariectomized control fed with normal diet (Ovx +N), ovariectomized rats fed with 2% cholesterol diet (Ovx + Cho) for four weeks. At the end of the study, the food intake and body weight were measured. The systolic, diastolic and mean blood pressure was determined. OVX+Cho showed significant increase in physiological changes such as body weight and food intake compared to Ovx+N group. The significant increase in systolic, diastolic and mean blood pressure was observed in Ovx+Cho group. Based on the above findings, it is believed that feeding cholesterol diet for four weeks (short term) results in significant increase in the blood pressure, food intake and body weight in the ovariectomised rats.